BMP signaling in the development and regeneration of tooth roots: from mechanisms to applications - Liu, Cangwei; Guo, Hao; Shi, Ce; Sun, Hongchen (Frontiers in Cell and Developmental Biology, 2023)
Short root anomaly (SRA), along with caries, periodontitis, and trauma, can cause tooth loss, affecting the physical and mental health of patients. Dental implants have become widely utilized for tooth restoration; however, they exhibit certain limitations compared to natural tooth roots. Tissue engineering-mediated root regeneration offers a strategy to sustain a tooth with a physiologically more natural function by regenerating the bioengineered tooth root (bio-root) based on the bionic principle. While the process of tooth root development has been reported in previous studies, the specific molecular mechanisms remain unclear. The Bone Morphogenetic Proteins (BMPs) family is an essential factor regulating cellular activities and is involved in almost all tissue development. Recent studies have focused on exploring the mechanism of BMP signaling in tooth root development by using transgenic animal models and developing better tissue engineering strategies for bio-root regeneration. This article reviews the unique roles of BMP signaling in tooth root development and regeneration.